Principales factores asociados a vaginosis bacteriana en mujeres en edad fertil que acuden al Hospital Universitario de Motupe en el periodo enero-julio 2016. - Pauta Cango, Gabriela Eloisa (2017)
Vulvovaginal infections are a major cause of consultation in units of primary and specialized medical care, bacterial vaginosis is the main vulvovaginitis that occurs most often, bacterial vaginosis is a vaginal infection caused by the abnormal proliferation of natural bacteria in the vagina, being the main cause of vaginal discharge in women of childbearing age. In the city of Loja in 2013 has there been a lot of morbidity, vulvovaginitis being in fifth place in the list of morbidity, with a total of 4924 patients, of which 3751 come to consulted for bacterial vaginosis, it is why it is believed convenient to carry out research on the main factors associated with the presence of bacterial vaginosis. The objective of this study is to investigate which are the main factors associated with the presence of bacterial vaginosis because currently there are no investigations in our city; in turn seeks to determine the relationship of the presentation of bacterial vaginosis with factors such as the onset of sexual activity, multiple sexual partners, not using barrier methods of contraception and pregnancy. For this study were included 59 users who met the inclusion criteria , where it was observed by the medical record their gynecological and obstetric history was used; the data were processed and then are expressed in tables and graphs using the program Microsoft Excel 2010 and then translate their analysis and interpretation. In the studied population it was found that the main factors associated with bacterial vaginosis are the onset of sexual activity, multiple sexual partners, not using barrier contraceptive methods and pregnancy is not a factor associated with this disease. Keywords: associated factors, bacterial vaginosis.